2010
DOI: 10.1089/vbz.2009.0173
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Group 2 Coronaviruses in a Bat Species Common to Urban Areas in Western Europe

Abstract: Fecal samples of 211 bats representing 13 different bat species from 31 locations in the Netherlands were analyzed for the presence of coronaviruses (CoV) using a genus-wide reverse transcription (RT)-polymerase chain reaction. CoVs are known for their high potential for interspecies transmission, including zoonotic transmission with bats as reservoir hosts. For the first time, a group 2 CoV was found in a bat, Pipistrellus pipistrellus, in Europe. This is of particular interest for public health as the reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 22 publications
6
65
1
2
Order By: Relevance
“…The evolutionary origins of MERS-CoV and related viral species belonging to the genus Betacoronavirus clade C were attributed to insectivorous bats in Europe and Africa ( 2 4 ). Seroprevalence studies of livestock from diverse species showed that dromedary camels from Oman, Saudi Arabia, the United Arab Emirates, Jordan, Qatar, Spain, and Egypt harbored antibodies against MERS-CoV antigens ( 5 8 ).…”
mentioning
confidence: 99%
“…The evolutionary origins of MERS-CoV and related viral species belonging to the genus Betacoronavirus clade C were attributed to insectivorous bats in Europe and Africa ( 2 4 ). Seroprevalence studies of livestock from diverse species showed that dromedary camels from Oman, Saudi Arabia, the United Arab Emirates, Jordan, Qatar, Spain, and Egypt harbored antibodies against MERS-CoV antigens ( 5 8 ).…”
mentioning
confidence: 99%
“…SARS CoV has a bat reservoir (Cui et al 2007), and the closest relative of MERS CoV (VM314/2008 betacoronavirus) was isolated from a Pipistrellus sp. bat in the Netherlands (Reusken et al 2010). The MERS CoV and VM314/2008 share 98% nucleotide identity in an 816-base pair (bp) fragment of the RNAdependent RNA polymerase (RdRp) gene and homologies in a 131-bp fragment of the spike receptor-binding domain Annan et al 2013).…”
mentioning
confidence: 99%
“…Similar results were obtained when conducting serological tests: pseudoparticle neutralization (ppNT), microneutralization (MNT) and ELISA for the presence of anti-MERS-CoV antibodies in camels sera acquired from the United Arab Emir-ates in 2005(Alexandersen et al, 2014 and the area of Egypt and Saudi Arabia in 2010(Hemida et al, 2013. In the seroepidemiological study of domestic livestock (sheep, goats, cattle, chicken) and dromedary camels from Saudi Arabia, it was shown that only dromedary camels have evidence of seropositivity to Middle East Respiratory Syndrome coronavirus (MERS-CoV), suggesting an infection with a MERS-CoV-like virus.…”
Section: Mers-cov Infections In Camelsmentioning
confidence: 58%